2010
DOI: 10.1021/pr9008964
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Rodent Ribosomes Revealed Heterogeneity Including Ribosomal Proteins L10-like, L22-like 1, and L39-like

Abstract: Heterogeneity of ribosome structure, due to variations in ribosomal protein composition, has been shown to be of physiological significance in plants and yeast. Mammalian genomics have demonstrated numerous genes that are paralogous to genes encoding ribosomal proteins. Although the vast majority are considered to be pseudogenes, mRNA expression of a few paralogues, such as human ribosomal protein L39-like/L39-2, has been reported. In the present study, ribosomes from the liver, mammary gland, and testis of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 69 publications
4
85
0
1
Order By: Relevance
“…RPL10L is expressed almost exclusively in testis, as has been observed biochemically (Sugihara et al 2010). RPL3L is highly expressed in heart and skeletal muscle, but barely at all elsewhere.…”
Section: Stoichiometry Of Mrnas Encoding Rpsmentioning
confidence: 54%
See 1 more Smart Citation
“…RPL10L is expressed almost exclusively in testis, as has been observed biochemically (Sugihara et al 2010). RPL3L is highly expressed in heart and skeletal muscle, but barely at all elsewhere.…”
Section: Stoichiometry Of Mrnas Encoding Rpsmentioning
confidence: 54%
“…This partially makes up for a substantial reduction in transcripts of RPL3 in those tissues. Because of the overall similarity of the "Like" proteins with their parents, we assume that they can take their place in the ribosome, as has been shown directly for L10L, L22L, and L39L (Sugihara et al 2010;Stadanlick et al 2011). Thus, one of the most intriguing results from the tissue comparisons in Supplemental Tables S6 and S7 is that there are clearly distinct tissue differences in ribosomes, e.g., L3L has likely replaced L3 in ∼25% of the ribosomes of muscle tissue.…”
Section: Stoichiometry Of Mrnas Encoding Rpsmentioning
confidence: 89%
“…The reduction of cyclin B levels causes G 2 arrest by p53-dependent transcriptional repression [34]. Incenp was shown to interact with Aurora B and survivin to form an Aurora B/incenp/survivin complex that is required for normal chromosome segregation [35][36][37]. It was reported that over-expressing survivin reduced p53 protein levels due to enhanced p53 degradation resulting from survivin-mediated inhibition of Mdm2 cleavage by caspases.…”
Section: Expression Alteration Of Cell Cycle Regulators In L8-depletementioning
confidence: 99%
“…As a homolog of ribosomal protein L39, ribosomal protein L39-L(RPL39-L) is normally expressed in the human testis and derepressed in multiple cancer cells (Nadano et al, 2002;Sugihara et al, 2010). Even so, the relationship between the function of RPL39-L and cancer cell drug resistance has not been confirmed now.…”
Section: Introductionmentioning
confidence: 99%